Descriptive Analysis of Building Partnership Network in the Concept of Management Towards Non-Formal Educational Institution at Pkbm Ziona in 2023/2024 - Gea, Devi Perdana Putri; Zebua, Elwin P.; Zega, Riswan; Harefa, Afore T. (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research aimed to determine the concept of partnership management occured at PKBM Ziona with partner institutions. This research was descriptive research with a qualitative approach. The data source were the Head of PKBM Ziona and a staff member. Data collection techniques were observation, interviews and documentation with interview guide and documentation guide instruments. Data analysis used Miles and Huberman which includes data collection, data reduction, data presentation, as well as drawing conclusions and verification. The research results showed that: : 1). The process of partnership they did were mapping, digging and collecting information, analyzing information, cooperation exploration, making agreements, signing of Memorandum of Understanding (MOU), implementation of activities, monitoring and evaluation, improvement, and further planning; 2). The concept of partnership management they did in some stages, namely (1) Partnership planning; (2) Implementation of the partnership includes realizing internal partnership activities industrial culture programs, as well as communication and coordination carried out by stakeholders who play a role; (3) Partnership evaluation includes monitoring and evaluation, reporting partnership activities, analysis of supporting factors and factors inhibiting partnerships include efforts to overcome obstacles, determination achievement of the objectives of partnership activities, benefits of partnerships, and development partnership. Both sides parties seek cooperation that is mutually helpful, complementary, and mutually beneficial. The collaboration that occurred has gone well and been successful.